Acute stress or systemic insulin injection increases flunitrazepam sensitive-GABAA receptor density in synaptosomes of chick forebrain: Modulation by systemic epinephrine - Cid, Mariana Paula (2009)
Interactions between acute stress and systemic insulin and epinephrine on GABAA receptor density in the forebrain were studied. Here, 10 day-old chicks were intraperitoneally injected with insulin, epinephrine or vehicle and then immediately stressed by partial water immersion for 15 min and killed by decapitation. Non-stressed controls were similarly injected, then returned to their rearing boxes for 15 min and then killed. Forebrains were dissected and GABAA receptor density was measured ex vivo in synaptosomes by 3[H]-flunitrazepam binding assay. In non-stressed chicks, insulin at 1.25, 2.50 and 5.00 IU/kg of body weight (non-hypoglycemic doses) increased Bmax by 33, 53 and 44% compared to saline, respectively. A similar increase of 41% was observed in receptor density after stress. However, the insulin effect was not additive to the stress-induced increase suggesting that both effects occur through similar mechanisms. In contrast, epinephrine, at 0.25 and 0.5 mg/kg did not induce any changes in Bmax in non-stressed chicks. Nevertheless, after stress these doses increased the receptor density by about 13 and 27%, respectively. Similarly, the same epinephrine doses co-administered with insulin (2.50 IU/kg), increased the receptor density by about 20% compared to insulin alone. These results suggest that systemic epinephrine, perhaps by evoking central norepinephrine release, modulates the increase in forebrain GABAA receptor binding induced by both insulin and stress. © 2008 Informa UK Ltd.